Tables for the calculation of friction in internal flows - Wallingford, H. R. (Thomas Telford ; American Society of Civil Engineers [distributor], 1995)
This system of tables derives from that adopted in Volume II of the 6th edition of the "Wallingford Table". In providing table-based aid for solution of the Colebrook-White equation, it extends to variation in kinematic viscosity, the incremental approach, a feature of the Wallingford Tables.